2018
DOI: 10.1002/ente.201800506
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Electrochemical Performance of Nickel Rich LiNi0.8Co0.1Mn0.1O2 Cathode by Lithium Aluminates Surface Modifications

Abstract: Ni‐rich layered compounds are very promising cathodes for lithium ion batteries whose surface modifications are normally required. As excellent lithium‐conducting solid electrolytes lithium aluminates such as LiAlO2 are expected to have an important role to play as a candidate for surface modifications. Here, Ni‐rich layered LiNi0.8Co0.1Mn0.1O2 (NCM) coated by lithium aluminates with different nominal weight percentages was prepared using a sol‐gel method. Lithium aluminates are found to be a mixture of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 46 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Particularly, the increase in the Ni content results in the increased specific capacity; however, at the same time, it deteriorates the structural and cycling stability because of the cation mixing, multiple phase transitions, and mechanical failure during delithiation and decreases the safety due to the enhanced possibility of thermal runaway. Due to an unavoidable tradeoff between capacity and safety, the attempts to simultaneously improve both properties in phase-pure NCM materials are futile . The efficient optimization strategies therefore include either doping of the host structure with multivalent cations or the formation of more complex morphologies with full or partial concentration gradients, surface coatings, , or core–shell structures. In particular, doping is well known to stabilize Ni-rich NCM-based cathode materials during extended lithium extraction and insertion. The advantage of most dopants lies in higher M–O bond dissociation energies, which hinder oxygen release and mitigate the corresponding structural changes as well as the resulting volume change and microcrack formation during long-term cycling of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the increase in the Ni content results in the increased specific capacity; however, at the same time, it deteriorates the structural and cycling stability because of the cation mixing, multiple phase transitions, and mechanical failure during delithiation and decreases the safety due to the enhanced possibility of thermal runaway. Due to an unavoidable tradeoff between capacity and safety, the attempts to simultaneously improve both properties in phase-pure NCM materials are futile . The efficient optimization strategies therefore include either doping of the host structure with multivalent cations or the formation of more complex morphologies with full or partial concentration gradients, surface coatings, , or core–shell structures. In particular, doping is well known to stabilize Ni-rich NCM-based cathode materials during extended lithium extraction and insertion. The advantage of most dopants lies in higher M–O bond dissociation energies, which hinder oxygen release and mitigate the corresponding structural changes as well as the resulting volume change and microcrack formation during long-term cycling of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution transmission electron microscope (HRTEM) images showed that the thickness of the coating layer was 5-7 nm for 1 wt.% LiAlO 2 coated LiNi 0.8 Mn 0.1 Co 0.1 O 2 . The structural stability of LiNi 0.8 Mn 0.1 Co 0.1 O 2 was enhanced by using LiAlO 2 coating, and it led to a capacity retention of 89.1% after 50 cycles at 280 mA g −1 within 2.5-4.5 V, which was higher than pristine NCM (82.5% capacity retention) [200]. XRD results indicated that the intensity ratio of I (003) /I (104) increased after LiAlO 2 surface modification.…”
Section: The Group Iiia Metal Oxides (Mox M = B Al)mentioning
confidence: 96%
“…In some studies, surface modification (i.e., surface coating and doping) has been utilized to stabilize the interface and address the aforementioned challenges. ,, Surface doping, by substituting the original ions with cations or anions such as B, Ti, Ta, Ce, V, Mg, and F, , aims to ensure steady the structure of Ni-rich cathode and enhance the lithium-ion diffusion kinetics. Surface coating is also an effective approach to achieve superior electrochemical performances due to protecting the Ni-rich cathode from HF, cleaning the detrimental surface functional groups (i.e., Li 2 O, LiOH, or Li 2 CO 3 ) and stabilizing the cathode/electrolyte interface as the conducting media for Li ion and electron. , Over the past decade, metal oxides (TiO 2 , ZnO, SiO 2 , ZrO 2 , Al 2 O 3 , and V 2 O 5 ), fluorides (AlF 3 ), and phosphates (MnPO 4 ) have been used as coating layers materials for LiNi 1– x – y Co x Mn y O 2 to protect the structure of the Ni-rich cathode from electrolyte. Among them, metal oxide, particularly Al 2 O 3 , has been widely coated onto electrode materials with success in varying degrees. Recently, oxide materials with high current endurance and low threshold electric field have aroused extensive attention in batteries, such as WO 3 , and SnO 2 , which may yield a better performance than Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%